Measures and applications of the Turkish Ice Hockey Federation during the COVID-19 pandemic - Kurudirek, M. I.; Kurudirek, M. A. (African Educational Research Journal, 2021)
COVID-19 virus, which broke out in Wuhan city of China in 2019 and has nearly brought the sports industry to a standstill, has spread to all stages within the organizational structure of sports. In this period, it can be said that sports clubs were affected economically, and coaches, managers and other stakeholders remained inactive. In this period, issues such as the creation of financial support packages for sports clubs and online education came to the fore. Therefore, strategies and applications of sports federations which are the competent authority of sports in the national platform, in this process have become a determinant for most work areas such as sports clubs, coaches, executives and referees to sustain their activities. This study was conducted to examine the education, development and health applications followed by the Turkish Ice Hockey Federation during the COVID-19 pandemic. In this study, the general screening method was used. It is expected that the applications carried out in the 2019-2020 and 2020-2021 seasons will set an example for other sports organizations.